$P(x)$ is an odd polynomial. When $(x−3)$ is factored out, the remainder is $6$. What is the remainder when $P(x)$ is divided by $(x^2-9)$?

Using the remainder theorem, when $x=3$, $P(x)=6$, and if the function is odd then when $x=-3$, $P(x)=-6$.

I would very much appreciate if someone can guide me through the solving process, since that is what I care about the most. Thanks in advance.


Since you asked for a bit of guidance...

In general, if we divide a degree $n$ polynomial $p(x)$ by a degree $m<n$ polynomial $d(x)$, we will end up with a degree $n-m$ polynomial $q(x)$ and a degree $m-1$ (at most) remainder $r(x)$. (This follows from the division algorithm - it might help to perform a few long or synthetic divisions on some polynomials just to play around with this idea.)

We can now express $p$ in terms of $d$, $q$ and $r$ as:

$$\overbrace{p(x)}^{\text{degree }n}=\underbrace{q(x)}_{\text{degree } n-m}\overbrace{d(x)}^{\text{degree }m}+\underbrace{r(x)}_{\text{degree }m-1\text{ (at most)}}$$

In the problem that you present, they give us that when $p(x)$ is divided by $d(x)=x-3$, the remainder is $6$. By the remainder theorem, we can conclude $p(3)=6$.

Since we are told that $p$ is an odd function, $p(-3)=-p(3)=-6$.

We are asked for the remainder when $p(x)$ is divided by $x^2-9=(x+3)(x-3)$. Notice that this is a degree $2$ polynomial, so the remainder will be a degree $1$ (linear) polynomial. In other words, $r(x)$ will have the form $ax+b$.

Expressing $p(x)$ in terms of this new information, then:


where $q$ is some polynomial.

From this, we can see that $p(3)=3a+b$, which we know is $6$, and $p(-3)=-3a+b$, which we know is $-6$. Solving these simultaneously gives us $a=2$ and $b=0$. Thus the remainder is the degree $1$ polynomial $2x$.

  • $\begingroup$ Very clear explanation, thank you. $\endgroup$ – user574848 Sep 26 '18 at 11:48

Hint: by euclidian division $p(x) = (x^2-9) q(x) + a x + b$.

Then $p(3)-p(-3)= 6a = 6 - (-6) = 12$ so $a=2$.

Since $p(x)$ is odd, all coefficients of even powers of $x$ are $0$, including the free term, so $b=0$.

So the remainder is $\cdots$


Hint: the linked question is quite useful for your purpose actually. Let $ax+b$ be the remainder when $p(x)$ is divided by $x^2-9$: $$ p(x)=(x^2-9)q(x)+ax+b. $$ We know \begin{aligned} 6\color{blue}{=}p(3)=0q(3)+3a+b&\implies 3a+b=6,\\ -6=-p(3)\color{blue}{=}p(-3)=0q(-3)+(-3)a+b&\implies-3a+b=-6 \end{aligned} The $\color{blue}{\text{colored}}$ bits above are where you use the given information.

So, two equations, two unknowns ($a$ and $b$), can you continue?


By the Division Algorithm for polynomials, the remainder has the form $ax+b$ for constants $a, b$. Hence, we have:$$p(x)=(x^2-9)q(x)+ax+b\implies 6=3a+b;-6=-3a+b$$, where $q(x)$ is a polynomial of degree $2$ less than $p(x)$ . Solving the two equations obtained for $a, b$; we obtain the remainder as $2x$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.